Achieving High Rate and Long Cycle Performance of Na2FePO4F Cathode Through Co‐Modification of Ti Doping and Carbon Coating - Deng, Ze‐Rong; Zhang, Lu‐Lu; Pei, Feng; Liu, Wen; Sun, Chang; Sun, Hua‐Bin; Ding, Xiao‐Kai; Yang, Xue‐Lin (Small (Weinheim an der Bergstrasse, Germany), 2024)
Layered Na2FePO4F (NFPF) cathode material has received widespread attention due to its green nontoxicity, abundant raw materials, and low cost. However, its poor inherent electronic conductivity and sluggish sodium ion transportation seriously impede its capacity delivery and cycling stability. In this work, NFPF by Ti doping and conformal carbon layer coating via solid‐state reaction is modified. The results of experimental study and density functional theory calculations reveal that Ti doping enhances intrinsic conductivity, accelerates Na‐ion transport, and generates more Na‐ion storage sites, and pyrolytic carbon from polyvinylpyrrolidone (PVP) uniformly coated on the NFPF surface improves the surface/interface conductivity and suppresses the side reactions. Under the combined effect of Ti doping and carbon coating, the optimized NFPF (marked as 5T‐NF@C) exhibits excellent electrochemical performance, with a high capacity of 108.4 mAh g−1 at 0.2C, a considerable capacity of 80.0 mAh g−1 even at high current density of 10C, and a high capacity retention rate of 81.8% after 2000 cycles at 10C. When assembled into a full cell with a hard carbon anode, 5T‐NF@C also show good applicability. This work indicates that co‐modification of Ti doping and carbon coating makes NFPF achieve high rate and long cycle performance for sodium‐ion batteries. Although layered Na2FePO4F has received widespread attention due to its nontoxicity, abundant raw materials, and low cost, its poor electronic conductivity and sluggish sodium ion transportation seriously hinder its capacity delivery and cycling stability. Herein, a co‐modification of titanium doping and carbon coating is proposed to enable Na2FePO4F to achieve high rate capacity and long cycle life in sodium‐ion batteries.